The squatters of Dhaka city: dynamism in the life of agargaon squatters - Paul-Majumder, Pratima; Mahmud, Simeen; Afser, Rita (Dhaka : The University Press Ltd., 1996)
General Collection
Keywords: The squatters; Dhaka City; Dynamism; Occupation; Income and earning